The Chinese Service Industry as a Challenge for European SME: A Systematic Approach for Market Entry - Schmitt, R.; Schumacher, S.; Scharrenberg, C. (Cranfield University Press, 2009)
Compared to industrial firms, the market share of foreign companies in the Chinese service industry is rather low. Especially western small and medium-sized service providing enterprises face different problems when they try to establish a business in China. Therefore an approach has been developed within a research project, which aims to support these companies in planning and successfully realising a service market entry in China. Methods are presented, which allow a systematic benchmark and selection of the target markets and a detailed definition and agreement of the cooperation between the Chinese and the western company.
Organised by: Cranfield University
Keywords: Internationalisation; Service; China